Diagnostic Evaluation of Hair Loss: A Narrative Review - Abena Minta; Lucy Rose; Sonja Kobayashi; Brittany Dulmage (European Medical Journal, 2023)
The psychosocial impact of alopecia on the quality of life of patients underscores the importance of dermatologist readiness to evaluate this common chief complaint. When evaluating a patient presenting with new-onset hair loss, the differential diagnosis may be broad, encompassing many subtypes of hair loss. Each type of scarring or non-scarring alopecia presents with its own unique aetiology, epidemiology, clinical presentation, trichoscopic findings, and laboratory studies. Further, accurate diagnosis is needed to determine appropriate therapeutic management. This review provides a systematic approach for dermatologists to use in order to accurately diagnose hair loss disorders, including clinical examination, laboratory evaluation, and specialised tests.